Rod photoreceptor-specific deletion of cytosolic aspartate aminotransferase, GOT1, causes retinal degeneration - Subramanya, Shubha; Goswami, Moloy T.; Miller, Nicholas; Weh, Eric; Chaudhury, Sraboni; Zhang, Li; Andren, Anthony; Hager, Heather; Weh, Katherine M.; Lyssiotis, Costas A.; Besirli, Cagri G.; Wubben, Thomas J. (Frontiers in Ophthalmology, 2023)
Photoreceptor cell death is the cause of vision loss in many forms of retinal disease. Metabolic dysfunction within the outer retina has been shown to be an underlying factor contributing to photoreceptor loss. Therefore, a comprehensive understanding of the metabolic pathways essential to photoreceptor health and function is key to identifying novel neuroprotective strategies. Glutamic-oxaloacetic transaminase 1 (Got1) encodes for a cytosolic aspartate aminotransferase that reversibly catalyzes the transfer of an amino group between glutamate and aspartate and is an important aspect of the malate-aspartate shuttle (MAS), which transfers reducing equivalents from the cytosol to the mitochondrial matrix. Previous work has demonstrated that the activity of this enzyme is highest in photoreceptor inner segments. Furthermore, ex vivo studies have demonstrated that the retina relies on aspartate aminotransferase for amino acid metabolism. Importantly, aspartate aminotransferase has been suggested to be an early biomarker of retinal degeneration in retinitis pigmentosa and a possible target for neuroprotection. In the present study, we characterized the effect of Got1 deletion on photoreceptor metabolism, function, and survival in vivo by using a rod photoreceptor-specific, Got1 knockout mouse model. Loss of the GOT1 enzyme from rod photoreceptors resulted in age-related photoreceptor degeneration with an accumulation of retinal aspartate and NADH and alterations in the expression of genes involved in the MAS, the tricarboxylic acid (TCA) cycle, and redox balance. Hence, GOT1 is critical to in vivo photoreceptor metabolism, function, and survival.